(untitled) - Cable, Daniel M. (Boston, 2018)
In Alive at Work, social psychologist Dan Cable argues that the reason for all the unhappiness is biological: organizations, in an effort to routinize work and establish clear-cut performance metrics, are suppressing what neuroscientists call our seeking systems, the part of our brain that craves exploration and learning.
Keywords: Sự thúc đẩy nguồn nhân lực,Sở thích (Tâm lí học),Employee motivation,Interest (Psychology)